34.9k views
2 votes
How to solve using Substitution or Elimination??? Help!!
y=3x-1

y=2x+2

User Beans
by
5.2k points

2 Answers

4 votes

Answer:


x=3


y=8

Explanation:

From these two equations, we can substitute the first equation into the second equation (or the other way round). This gives us:


3x-1=2x+2


3x-2x=2+1 (minus
2x and add
1 on both sides)


x=3

To solve for
y, we can use substitution again:


y = 3(3)-1 (using the first equation given)


y=8

Hope this helps :)

User Nalply
by
5.4k points
6 votes

Answer:

Explanation:

Since both equations equals y, then both equations equal each other.

3x - 1 = 2x + 2

Subtract 2x from both sides

x - 1 = 2

Add 1 to both sides

x = 3

Plug x = 3 into one equation(doesn't matter which)

y = 3x - 1

y = 3(3) - 1

y = 9 - 1

y = 8

User Rashleighp
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.